Factors Affecting Gestation Length in Gir Cattle - Parikh, Suryakant S.; Savaliya, Bhagvanji D.; Patbandha, Tapas K.; Makwana, Rinkesh B.; Gamit, Pranav M.; Parmar, Monika R. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was planned to understand the factors affecting gestation length in nulliparous and pluriparous Gir cows. A cumulative ten years (2010-2019) full term calving record (n = 1272) of Gir cows were incorporated. The overall mean gestation length of Gir cattle was 283.29 ± 0.16 days. It was shortest in 8th and above parities and longest in 7th parity Gir cows (282.39 and 285.84 days, respectively); with statistically significant (p<0.05) difference. The gestation length remained almost similar from nulliparous to 6th parities cows (ranged from 283.10 to 283.74 days) and the values were more or less close to the overall mean of gestation length. The mean gestation length in cows having female calf was 1.4 days shorter than those with male calf (282.60 vs. 283.99 days). There was period wise significant variation of gestation length in Gir cows (p<0.05). The Gir cattle served during December and March had shortest and longest mean gestation length (282.22 and 284.40 days), respectively; the difference was statistically significant (p<0.05). The mean gestation length across different calving months varied significantly (p<0.05). Season of service and season of birth did not affect gestation length in Gir cattle. The results showed that Gir cows are less affected for gestation length by different factors throughout the year.